Politics of culturalism in an age of globalisation: discrimination, discontent and dialogue - Bharucha, Rustom (1999)
The intercultural, the multicultural and the global inhabit different yet overlapping narratives that should not be arbitrarily conflated. There is a crisis of practice in much philosophical and social scientist thinking on multiculturalism and an insufficient engagement of philosophers with emergent cultural practices. This article attempts to intersect political philosophy and cultural practice. While multiculturalism works within the cultural logic of multinational capital, interculturalism has the potential to work against this logic. - Reproduced
Keywords: Intercultural communication; Multiculturalism